2008
DOI: 10.1177/1087054708320441
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Symptomatology and Its Relationship to Factors Associated With College Adjustment

Abstract: Objective: The present study assessed the relationship between self-reported ADHD symptomatology in college students and various factors that are associated with persistence in college. Method: A total of 321 students completed questionnaires examining ADHD symptoms, academic and social adjustment to college, career decision-making self-efficacy, study skills, and GPA. Results: Analyses indicated that higher levels of ADHD symptoms were significantly related to lower levels of career decision-making self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
84
0
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 29 publications
9
84
0
11
Order By: Relevance
“…Although ADHD must first manifest in childhood to warrant diagnosis, numerous longitudinal research studies have shown that the symptoms of this disorder rmay continue into adulthood (Barkley, 1998;Shekim, Asarnow, Hess, Zaucha, & Wheeler, 1990). ADHD affects 2% and 11% of the college student population (DuPaul, Weyandt, O'Dell, & Varejao, 2009;Weyandt & DuPaul, 2008), and college students who are diagnosed with ADHD are at increased risk of being placed on academic probation, having a lower grade point average, experiencing more academic problems, and failing repeatedly than are students without this disorder (Blasé et al, 2009;Heiligenstein, Guenther, Levy, Savino, & Fulwiler, 1999;Norvilitis, Sun, & Zhang, 2010;Norwalk, Norvilitis, & MacLean, 2009). Despite these potential academic difficulties, young adults with ADHD are enrolling in postsecondary education in increasing numbers (Dipeolu, 2011;DuPaul et al, 2009;Weyandt & DuPaul, 2008), and all higher education institutions are mandated by federal law (Section 504 of the Rehabilitation Act, 1977) to provide services and accommodations to ensure success in the academic and career pursuits of these students.…”
mentioning
confidence: 99%
“…Although ADHD must first manifest in childhood to warrant diagnosis, numerous longitudinal research studies have shown that the symptoms of this disorder rmay continue into adulthood (Barkley, 1998;Shekim, Asarnow, Hess, Zaucha, & Wheeler, 1990). ADHD affects 2% and 11% of the college student population (DuPaul, Weyandt, O'Dell, & Varejao, 2009;Weyandt & DuPaul, 2008), and college students who are diagnosed with ADHD are at increased risk of being placed on academic probation, having a lower grade point average, experiencing more academic problems, and failing repeatedly than are students without this disorder (Blasé et al, 2009;Heiligenstein, Guenther, Levy, Savino, & Fulwiler, 1999;Norvilitis, Sun, & Zhang, 2010;Norwalk, Norvilitis, & MacLean, 2009). Despite these potential academic difficulties, young adults with ADHD are enrolling in postsecondary education in increasing numbers (Dipeolu, 2011;DuPaul et al, 2009;Weyandt & DuPaul, 2008), and all higher education institutions are mandated by federal law (Section 504 of the Rehabilitation Act, 1977) to provide services and accommodations to ensure success in the academic and career pursuits of these students.…”
mentioning
confidence: 99%
“…São poucos os pacientes que têm que interromper o uso por manifestação de efeitos colaterais, como insônia, diminuição do apetite, irritabilidade, perda de peso, dores abdominais e/ou cefaleias [4][5][6] . No meio universitário, ainda não há um consenso sobre a prevalência de TDAH, porém foi visto nos EUA que os universitários com níveis clinicamente significativos de sintomas desse transtorno estão claramente associados a prejuízos no desempenho acadêmico, uso de álcool, tabaco e outras substâncias ilícitas 7 .…”
Section: Introductionunclassified
“…In sharp contrast, college students with ADHD symptoms are more likely to have negative beliefs about their performance (Shifrin, Proctor, & Prevatt, 2010) and experience high levels of anxiety when taking cognitive tests (Prevatt, Dehili, Taylor, & Marshall, 2015), even when they perform comparably to other students (Lewandowski, Gathje, Lovett, & Gordon, 2012). The inattentive symptoms of ADHD seem to be particularly associated with an undermined confidence in work and career planning and performance, possibly because these symptoms imply more accentuated executive functioning deficits than hyperactivity alone (Norwalk et al, 2009).…”
mentioning
confidence: 98%
“…With regard to the relationship with the university, students with ADHD symptoms tend to feel less attached and affiliated to their educational institutions (Shaw-Zirt et al, 2005), and they are more likely to engage in antisocial behavior (Gudjonsson, Sigurdsson, Adalsteinsson, & Young, 2013) and experience drinkingrelated problems (Mesman, 2015). Internal correlates of ADHD symptoms among college students include low selfesteem and emotional instability (Blase et al, 2009;ShawZirt et al, 2005), procrastination (Souza et al, 2008), and depression (Norwalk, Norvilitis, & MacLean, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation